Multidisciplinary collaborative model for identification and assessment services for students with special needs in inclusive schools - Taqiyah, Dewi Barotut; Hermanto, Hermanto; Ishartiwi, Ishartiwi; Pujaningsih, Pujaningsih (LPMPP Universitas Negeri Yogyakarta, 2025)
This study aims to understand the multidisciplinary collaboration among professionals who voluntarily participate and share common goals in implementing assessment and identification services for children with special needs. This collaboration involves a multidisciplinary team working to develop an assessment service model and recommendations from the multidisciplinary for assessing children with special needs in inclusive schools. This research is qualitative approach with a case study method. Data sources included psychologists, orthopedagog, medis, principals, teachers, and parents at an inclusive school in Yogyakarta, Indonesia. Data were collected through in-depth interviews, observations, and documentation. Data validation was performed using two triangulation techniques: source triangulation and method triangulation. The results show that assessment services for primary school children with special needs comprise three service models: educational assessment model, psychological assessment model, and medical assessment model. The preparation stage is divided into four activities: formulating goals, identifying targets, preparing instruments, and preparing for implementation. The implementation stage includes four aspects: approach, techniques, methods, and referral. The reporting stage is divided into two parts: result analysis and recommendations. The final stage, follow-up, is conducted through a case conference.